Buried channel normally-off AlGaN/GaN MOS-HEMT with a p-n junction in GaN buffer. (1st August 2018) - Soman, Rohith; Sharma, Manish; Ramesh, Nayana; Nath, Digbijoy; Muralidharan, R; Bhat, K N; Raghavan, Srinivasan; Bhat, Navakanta
Abstract: A buried channel normally-off AlGaN/GaN MOS-HEMT with gate recess etching is reported. The buried channel operation is achieved by in situ doping of GaN to introduce a p-n junction in the GaN buffer. The fabricated buried channel MOS-HEMT with 12.5 nm atomic layer deposition (ALD) Al2 O3 gate dielectric featured a threshold voltage of 1.3 V with a drain saturation current of 287 mA mm −1 for a device with 3.5 μ m long gate length and 11 μ m source-drain spacing. The field effect mobility improved from 25 cm 2 /Vs for a reference device to 142 cm 2 /Vs for the buried channel device. Due to the presence of the p-n junction depletion region in the GaN buffer, the leakage in the off state decreased by about 4 orders of magnitude (4 nA mm −1 compared to 76 uA mm −1 for the reference device). The buried channel device also gives better breakdown characteristics, with a breakdown voltage of 158 V compared to 98 V for the reference device.